Seagrass existence after Sunda Strait tsunami 2018: Evidence in Tanjung Lesung region. Issue 1 (January 2020) - Rahmawati, A; Khalifa, M A; Indaryanto, F R; Adrianto, L; Agus, S B; Kurniawan, F
Abstract: The volcanic tsunami occurred at the Sunda strait at the end of 2018. Tanjung Lesung is one of the affected areas, and the seagrass ecosystem allegedly affected too. This research aims to determine seagrass existence in Tanjung Lesung after the tsunami 2018. This research was conducted from June until July 2019 with the same area as the previous study (before tsunami). Observation method using 20 × 0.5 m belt transect sized 50 × 50 cm quadrat. The transect was made perpendicular to the beach line. Seagrass species that were found outside transect also noted. This research found six seagrass species in Tanjung Lesung after tsunami 2018; there were Enhalus acoroides, Cymodocea rotundata, C. serrulata, Syringodium isoetifolium, Halophila ovalis, and Thalassia hemprichii . The most significant impact of tsunami 2018 for seagrass existence sighted in the west part of the cape. Seagrass in the previous observation point has already disappeared and replaced with rock, dead coral, and macro-algae.